2019
DOI: 10.1002/bse.2319
|View full text |Cite
|
Sign up to set email alerts
|

Does gender diversity matter for green innovation?

Abstract: This study empirically investigated the relationship between board gender diversity and firm's green innovation, using panel data of public companies of China's manufacturing. Green product innovation was assessed by “green” patents and green process innovation assessed by environmental management certification. The endogeneity problem that resulted from self‐selection of gender diversity was addressed by means of extended probit regressions with an instrumental variable, and the instrumental variable was elab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 60 publications
10
159
1
Order By: Relevance
“…This is notably important for the environment, as the plaintiffs are general communities and the environment without contractual relationships with firms (Liu, 2018). Firms' commitment towards the environment is largely determined by the extent to which they consider the interests of broader stakeholder groups in policy-making (He & Jiang, 2019). Female directors are found to be more concerned about the interests of others and in maintaining long-term relationships (Nadeem et al, 2020).…”
Section: Bgd and Environmental Innovationmentioning
confidence: 99%
“…This is notably important for the environment, as the plaintiffs are general communities and the environment without contractual relationships with firms (Liu, 2018). Firms' commitment towards the environment is largely determined by the extent to which they consider the interests of broader stakeholder groups in policy-making (He & Jiang, 2019). Female directors are found to be more concerned about the interests of others and in maintaining long-term relationships (Nadeem et al, 2020).…”
Section: Bgd and Environmental Innovationmentioning
confidence: 99%
“…Nevertheless, existing research rarely mentions that whether and how the characteristics of CEOs play a role in firm outcomes that combine both innovation and CSR such as, in our context, green innovation. A few exceptions include studies on how executives' gender (He & Jiang, 2019), environmental concern (Tang, Walsh, Lerner, Fitza, & Li, 2018), hubris (Arena et al, 2018) and temporal cognition (Liao, 2016) facilitate the engagement in green innovation. However, none of these research has shed light on examining the influence of CEO hometown identity on firm green innovation, which we follow this line of research by.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Finally, firms with green patents represent specific characteristics that can affect the relationship between environmental and financial performance. For example, He and Jiang () found that the occurrence of green innovation at the firm level is systematically related to female board representation. On the other hand, Przychodzen et al () stated that firms possessing environmental innovations have some specific features such as a strong preference formation, higher complexity, and higher uncertainty compared to firms possessing nonenvironmental innovations.…”
Section: Theoretical Background and Hypotheses' Developmentmentioning
confidence: 99%